Impaired esophagogastric motor function as a predictor for development of hiatal hernia in military personnel - O.M. Babii; B.F. Shevchenko; N.V. Prolom; A.M. Halinska; О.О. Halinskyi (Gastroenterologìa)
Background. Disorders of esophagogastric motility, often associated with the development of hiatal hernia (HH), represent a common pathological condition. The characteristics of these functional changes may vary depending on lifestyle factors, levels of physical activity, and adaptive mechanisms, which differ between military personnel and civilians. Evaluation of such differences is essential for the development of individualized approaches to the diagnosis and treatment of HH. The purpose was to identify esophagogastric motility disorders as predictors of hiatal hernia development in military personnel by analyzing parameters obtained through digital pneumoballoon manometry. Materials and methods. Digital pneumoballoon manometry of the esophagus and stomach was performed in 66 patients with hiatal hernia (30 military personnel and 36 civilians, serving as the comparison group). The analysis included assessment of the amplitude and duration of peristaltic waves, rhythmic fluctuations of the esophageal wall, and pressure in the areas of the lower esophageal sphincter and pyloroduodenal sphincter. Results. The amplitude of the peristaltic wave in military personnel was 1.9 times higher than in civilians, whereas the wave duration in civilians was 40.5 % longer (p < 0.05). Rhythmic oscillations of the esophageal wall were less pronounced in civilians, suggesting more significant motility disorders. Pressure in the lower esophageal sphincter region was reduced by 50.7 % in military personnel (p < 0.05) and by 53.7 % in civilians (p < 0.01) compared to control values, contributing to the development of gastroesophageal reflux. Pressure in the pyloroduodenal sphincter region increased 2.2-fold in military personnel and 2.8-fold in civilians (p < 0.05). Conclusions. Assessment of esophagogastric motility using digital pneumoballoon manometry enables the identification of predictors of HH development in military personnel. The results underscore the need for a personalized approach to the treatment of hiatal hernia.